Squeezing the Nonprofit Sector - Levy, Daniel (International Higher Education, 2013)
The growth of the for-profit sector combines with a partial public sector resurgence to squeeze the nonprofit sector, which for decades had increased its global enrollment share. The for-profit growth relates to competitive advantages in prioritizing the labor market while the public move involves accelerated access missions, changing demographics, and policies of competitive marketization.